Validation of mathematical model with phosphate activation effect by batch (R)-phenylacetylcarbinol biotransformation process utilizing Candida tropicalis pyruvate decarboxylase in phosphate buffer - Julaluk Khemacheewakul (Nature Portfolio, 2021)
Abstract The (R)-phenylacetylcarbinol (PAC) batch biotransformation kinetics for partially purified Candida tropicalis TISTR 5350 pyruvate decarboxylase (PDC) were determined to validate a comprehensive mathematical model in 250 mL scale with 250 mM phosphate buffer/pH 7.0. PDC could convert initial 100/120 mM benzaldehyde/pyruvate substrates to the statistical significantly highest (p ≤ 0.05) maximum PAC concentration (95.8 ± 0.1 mM) and production rate (0.639 ± 0.001 mM min−1). A parameter search strategy aimed at minimizing overall residual sum of square (RSS T ) based on a system of six ordinary differential equations was applied to PAC biotransformation profiles with initial benzaldehyde/pyruvate concentration of 100/120 and 30/36 mM. Ten important biotransformation kinetic parameters were then elucidated including the zeroth order activation rate constant due to phosphate buffer species (k a ) of (9.38 ±  < 0.01) ×  10–6% relative PDC activity min−1 mM−1. The validation of this model to independent biotransformation kinetics with initial benzaldehyde/pyruvate concentration of 50/60 mM resulted in relatively good fitting with RSS T , mean sum of square error (MSE), and coefficient of determination (R2) values of 662, 17.4, and 0.9863, respectively.